Kingdom of Lesotho : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Lesotho is a small, landlocked, low-income country, with limited natural resources and a narrow production and export base. In recent Article IV consultations, IMF staff has emphasized the importance of ensuring that increases in outlays for poverty reduction are consistent with fiscal sustainability and absorptive capacity. However, economic activity has remained sluggish, reflecting the adverse impact of exogenous shocks. Fiscal management is becoming more challenging. The authorities are making efforts to implement their poverty reduction strategy. The political situation is relatively stable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet